2018
DOI: 10.1021/acs.est.7b06006
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future United States Light-Duty Vehicle Pathways: Cradle-to-Grave Lifecycle Greenhouse Gas Emissions and Economic Assessment

Abstract: This article presents a cradle-to-grave (C2G) assessment of greenhouse gas (GHG) emissions and costs for current (2015) and future (2025-2030) light-duty vehicles. The analysis addressed both fuel cycle and vehicle manufacturing cycle for the following vehicle types: gasoline and diesel internal combustion engine vehicles (ICEVs), flex fuel vehicles, compressed natural gas (CNG) vehicles, hybrid electric vehicles (HEVs), hydrogen fuel cell electric vehicles (FCEVs), battery electric vehicles (BEVs), and plug-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…In separate literature, researchers have assessed refueling station costs (34) and hydrogen delivery pathways (35). Furthermore, battery electric vehicles could cost less than FCEVs on a per mile basis, depending on trends in capital and fuel costs (36). Our study identifies the greatest challenges to reducing PEMFC production costs.…”
Section: Significancementioning
confidence: 99%
“…In separate literature, researchers have assessed refueling station costs (34) and hydrogen delivery pathways (35). Furthermore, battery electric vehicles could cost less than FCEVs on a per mile basis, depending on trends in capital and fuel costs (36). Our study identifies the greatest challenges to reducing PEMFC production costs.…”
Section: Significancementioning
confidence: 99%
“…Compared to the 2016 simulations, the latest simulations give a few percent greater energy use for the 2015 CV and HEV and advanced BEV, but about 20% less energy use for the 2015 BEV. The previous simulation results were used in Harvey (2018a) in an analysis of the future cost and performance of advanced vehicles and as an input to a complete lifecycle analysis by Elgowainy et al (2018) for the 2020–2025 time horizon.…”
Section: Vehicle Performance Potential and Regulationsmentioning
confidence: 99%
“…In a cradle-to-grave analysis, Algowainy et al [7] showed that a combination of engine technologies and renewable fuels could decrease the greenhouse gas emissions by 10-30% of their current amounts. Homogenous charge compression ignition (HCCI) engines are one of those technologies that could push the boundaries of the ICE efficiency [8].…”
Section: Introductionmentioning
confidence: 99%